NATURE OF NON-PARALYTIC AND TRANSITORY PARALYTIC POLIOMYELITIS IN RHESUS MONKEYS INOCULATED WITH HUMAN VIRUS - Sabin, Albert B. (The Rockefeller University Press, 1941)
1. The occurrence of non-paralytic poliomyelitis in monkeys inoculated with human or first passage virus was proved by histological examination of the nervous system and by isolation of the virus. 2. The non-paralytic infection was almost invariably associated with the destruction of an appreciable number of nerve cells in the spinal cord, and failure of the process to progress seemed to depend upon an equilibrium between the host and the virus, in which the latter occasionally persisted in an active state since it could produce the typical paralytic disease on passage to other monkeys. 3. While there were no reliable clinical or laboratory criteria, the diagnosis of non-paralytic poliomyelitis was made when the following changes were found in the spinal cord: (a) outfall of neurons confirmed by the presence of the reaction of degeneration in the nerve roots, and (b) foci of glial infiltration and perivascular cuffing in the gray matter. 4. Anterior horn cells showing diffuse chromatolysis and acidophilic, intranuclear inclusions were present 2 days after disappearance of paralysis of short duration, and nerve cells with marginated Nissl substance and eccentric nuclei were found side by side with obviously older lesions in monkeys with non-paralytic poliomyelitis. These cytologic changes were not present in monkeys sacrificed in still later stages of the disease. 5. The transitory character of the paralysis in some monkeys may depend in part on the fact that apparently normal function can be carried on with less than the normal number of nerve cells and in part on the probable, but not proved, possibility that not all nerve cells attacked by poliomyelitis virus are irreversibly damaged.